Uji Efektivitas Bioherbisida Ekstrak Daun Pepaya (Carica papaya L.) pada Gulma Babadotan (Ageratum conyoides L.) - Septiyani, Alda; Saylendra, Andree; Hilal, Samsu; Rumbiak, Julio E.R (Universitas Pattimura, 2025)
The excessive use of synthetic herbicides can have adverse effects on living organisms and the environment. Therefore, environmentally friendly weed control alternatives are needed, such as the use of bioherbicides. Papaya leaf extract contains allelopathic compounds including alkaloids, triterpenoids, steroids, flavonoids, saponins, tannins, and phenols that can inhibit weed growth. This study aimed to determine the effectiveness of papaya (Carica papaya L.) leaf extract as a bioherbicide in suppressing the growth of babadotan (Ageratum conyzoides L.) weeds. The study was conducted from February to May 2025 at the Bukit Kawi Permai Complex, Kramatwatu Village, Kramatwatu District, Serang Regency and the LPHP Region II Laboratory, Pandeglang. This study used a Completely Randomized Block Design (RBD) consisting of seven treatment levels, with four replications. The treatment levels included: P0-: negative control without herbicide, P0+: positive control herbicide (bispiribak sodium 18% and pyrazosulfuron 10%), P1: 30% extract, P2: 40% extract, P3: 50% extract, P4: 60% extract, and P5: 70% extract. The results showed that the administration of papaya leaf extract showed effectiveness as a bioherbicide in inhibiting the growth of babadotan weeds compared to the control. Administration of papaya leaf extract at a concentration of 60% and 70% had a very significant effect on fresh weight and had an effect on phytotoxicity of 13.35% (P4) and 17.5% (P5).